2010
DOI: 10.1016/j.ijmultiphaseflow.2010.07.004
|View full text |Cite
|
Sign up to set email alerts
|

The influence of multiple tubes on the tube-to-bed heat transfer in a fluidised bed

Abstract: a b s t r a c tThere have been few studies modelling both flow and heat transfer in fluidised beds. The kinetic theory of granular flow (KTGF) has been used for flow prediction in the past without heat transfer modelling. In the present study, a two-fluid Eulerian-Eulerian formulation incorporating the KTGF was applied first to a tube-to-bed reactor with one immersed tube and compared with the results in the literature. The bed was then modified to introduce two and three heated tubes. The effects on the flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Computational models predicting the heat-transfer coefficient in bubbling fluidised beds have also been carried out (Patil et al, 2006;Schmidt and Renz, 2000;Kuipers et al, 1992;Armstrong et al, 2010). The incorporation of the complex species transport equations and reactions within the coal gasification and combustion have been very limited due to the high computational cost of the models.…”
Section: Introductionmentioning
confidence: 99%
“…Computational models predicting the heat-transfer coefficient in bubbling fluidised beds have also been carried out (Patil et al, 2006;Schmidt and Renz, 2000;Kuipers et al, 1992;Armstrong et al, 2010). The incorporation of the complex species transport equations and reactions within the coal gasification and combustion have been very limited due to the high computational cost of the models.…”
Section: Introductionmentioning
confidence: 99%
“…It is found that the simulation value for =0.3 is closer to the experimental value. Therefore, the specularity coefficient 0.3, which is very close to = 0.25 used by Armstrong et al [30,54] , for the partial-slip boundary condition is selected to simulate the flow of gas and particles in two catalyst coolers. The selected specularity value is also consistent with the recommendations from Bakshi et al [55] , who suggested that values of shall be n the range of [0.01, 0.3] to simulate dense solid-gas flows.…”
Section: Specularity Coefficientmentioning
confidence: 99%
“…Zhao et al, [5] conducted simulations using the combined Computational Fluid Dynamics-Discrete Element Method (CFD-DEM) to analyse particle-particle and particle-fluid heat transfer behaviours by quantifying the contribution to heat transfer coefficient via convection, conduction, and radiation. Armstrong et al, [6] modelled one, two and three heated tubes immersed in fluidized bed reactors using an Eulerian-Eulerian kinetic theory of granular flow model. Teaters, [7] used a (CFD) with and without turbulence modelling to predict the gas-solid hydrodynamics of fluidized beds.…”
Section: Introductionmentioning
confidence: 99%